STUDY OF ENZYMURIA INDICATORS IN PATIENTS WITH RENAL DYSFUNCTION AND CHRONIC HEART FAILURE (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Chronic heart failure (CHF) is the most common, progressive, and unfavorable disease of the cardiovascular system, and is also the most frequent cause of patient hospitalization. According to the Framingham study, CHF incidence doubles every ten years. CHF significantly worsens patients' quality of life and increases the risk of death by up to 4 times. The annual mortality rate in patients can be 15-50%. The risk of sudden death in patients with CHF is 5 times higher than in those without chronic heart failure. The most common cause of CHF is ischemic heart disease (IHD), which accounts for 54-68.6% of patients with CHF (1,9). Myocardial infarction is one of the main causes of CHF development and is characterized by post-infarction remodeling of the left ventricle (LV): structural and functional restructuring of the LV and impairment of systolic and diastolic functions. CHF is one of the most important determinants in the development of chronic kidney disease (CKD). A number of retrospective studies have established that there is a correlation between the development of chronic heart failure (CHF) and renal dysfunction (RD), which leads to a deterioration in patients' lives (5,12). An increase in overall and cardiovascular mortality in CKD is observed even with a slight decrease in renal function and is especially pronounced in patients with cardiovascular diseases, including those with chronic heart failure (6,13). The results of epidemiological and population studies indicate that even subclinical impairment of renal function is an independent risk factor for cardiovascular complications (CVC) and mortality. It is evident that in CHF, the creatinine level is analogous to the ejection fraction and is an independent predictor of adverse outcomes (4,7). Patients with both CKD and CHF have a high risk of developing renal failure and require replacement therapy. The results of numerous epidemiological, prospective, retrospective, clinical, and specially planned studies show that severe renal dysfunction can cause various cardiovascular conditions, including myocardial infarction (MI), sudden death, cerebral ischemic stroke, and primary heart failure (10).